Analisis Tembaga (Cu) Dan Timbal (Pb) dalam Air Laut dan Sedimen di Perairan Pantai Loli Kecamatan Banawa Kabupaten Donggala - Santi, Santi; Tiwow, Vanny M. A.; Gonggo, Siang Tandi (Universitas Tadulako, 2017)
This study aimed to determine the concentration of heavy Cu and Pb in seawater and sediment in coastal waters Loli subdistrict Banawa, district Donggala. The method used was destruction and using Atomic Absorption Spectrophotometer (AAS) instrument.Samples of seawater and sediment were taken by two sampling points. Samples were destructed by using a solution of HNO3 and HClO4with ratio 4: 1. Levels were measured at a wavelength of 325.7 nm for Cu and 217 nm for Pb. The analysis result obtained that the levels of Pb in the seawater in the range of 0,531-0.671 mg/L, while for Cu in the range of 0.009-0.090 mg/L it can be concluded that the levels of Pb and Cu in seawater has exceeded the levels were of 0,008 mg/L. For sediment samples obtained that Pb levels were around 1,78-7,73 mg/kg while for Cu 15.86-68.88 mg/kg so Cu in sediment was up to 30 mg/kg while the levels of Pb did not exceed the tolerance limits of 33 mg/kg.